Studies on Tanzanian forest work. - Saarilahti, M.; Bakena, E.; Mboya, G.; Minja, T.; Ngerageze, T.; Ntahompagaze, J. (Silva Fennica, 1987)
Four teams of two workers were time-studied in clearcutting of a cypress plantation and three teams in sulky skidding. The heart rate was recorded every 30 s. The average heartrate in timber cutting was 117.5 Â± 13.4 P/min, and it was mainly dependent on workerâs working capacity. Average work load index was 41 Â± 3% when working at 97% performance. The production rate was then 2.5 m/h (crew). In sulky skidding the heart rate was lower, 106 Â± 1.1 P/min, as well as the work load (WLI 30 Â± 1%) and performance rating (87%). The low production rate (1.1 m/h) (crew)) over 45 m distance is mainly due to under-dimensioned load size. The energy expenditure in timber cutting was 21.4 kJ/min and in sulky skidding 16.3 kJ/min. Daily energy expenditure was 15.0 MJ/d, and most of the timber cutters belonged to the class âexceptionally activeâ.33